2018
DOI: 10.1002/eji.201847584
|View full text |Cite
|
Sign up to set email alerts
|

A clinically applicable adjuvant for an atherosclerosis vaccine in mice

Abstract: Vaccination with MHC-II-restricted peptides from Apolipoprotein B (ApoB) with complete and incomplete Freund's adjuvant (CFA/IFA) is known to protect mice from atherosclerosis. This vaccination induces antigen-specific IgG1 and IgG2c antibody responses and a robust CD4 T cell response in lymph nodes. However, CFA/IFA cannot be used in humans. To find a clinically applicable adjuvant, we tested the effect of vaccinating Apoe-deficient mice with ApoB peptide P6 (TGAYSNASSTESASY). In a broad screening experiment,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 60 publications
(72 reference statements)
0
20
0
2
Order By: Relevance
“…It has been proposed that either T regs 42, 164-167 , IL-10 42,161,167,168 , or vaccination-induced IgG-antibodies may confer atheroprotection, depending on doses, routes, and adjuvants used 44 . Recent studies, however, suggest that atheroprotection does not require IgG-antibodies 169 and primarily proceeds by IL-10 + ApoB-specific T regs 42 .…”
Section: Vaccination Against Atherosclerosis -A Translatable Strategy?mentioning
confidence: 99%
See 1 more Smart Citation
“…It has been proposed that either T regs 42, 164-167 , IL-10 42,161,167,168 , or vaccination-induced IgG-antibodies may confer atheroprotection, depending on doses, routes, and adjuvants used 44 . Recent studies, however, suggest that atheroprotection does not require IgG-antibodies 169 and primarily proceeds by IL-10 + ApoB-specific T regs 42 .…”
Section: Vaccination Against Atherosclerosis -A Translatable Strategy?mentioning
confidence: 99%
“…Subcutaneous or intraperitoneal injections of both, CFA and IFA, were shown to elicit nonspecific inflammation 171,172 . This limitation was recently overcome by the discovery that a squalene oil, a class of adjuvants already used in clinical practice, can be used as an adjuvant for ApoB-peptides 169 . In addition, it remains unclear whether vaccination is effective in established atherosclerosis as most studies tested the prevention of de-novo atherosclerosis in rodents.…”
Section: Vaccination Against Atherosclerosis -A Translatable Strategy?mentioning
confidence: 99%
“…This trial showed no evidence of efficacy of antibody treatment. In mouse models, it is known that vaccine-induced antibody responses are dispensable for atheroprotection 15 .…”
Section: Future Atherosclerosis Therapy and Preventionmentioning
confidence: 99%
“…Gegenwärtig werden hauptsächlich drei Wirkmechanismen diskutiert: Induktion von T regs (42,(164)(165)(166)(167), IL-10-Produktion (41,42,161,167) oder impfinduzierte IgG-Antikörper -abhängig von der Dosis, Administrationsroute und Adjuvantien (44). Neuere Studien legen nahe, dass IgG-Antikörper nicht notwendig sind (168), sodass die T reg und IL-10-Hypothesen wahrscheinlicher werden (42). Ob Arterioskleroseimpfungen für die klinische Anwendung entwickelt werden können, ist noch unklar.…”
Section: Kann Arterioskleroseimpfung Für Die Klinische Anwendung Entwunclassified
“…Beide Adjuvanzien können nicht beim Menschen angewandt werden, da die subkutane oder intraperitoneale Injektion von CFA oder IFA starke unspezifische Entzündung induziert (170,171). Dieses Problem wurde in einer neueren Studie gelöst, in der gezeigt wurde, dass ein Squalenöl, ein Adjuvans das bereits in klinischen Impfstoffen benutzt wird, mit ApoB-Peptiden gegeben werden kann und effektiv vor Arteriosklerose schützt (168). Derzeit ist außerdem unbekannt, ob Impfung von Nagetieren mit bereits bestehender Arteriosklerose wirkt, da die meisten Studien nur die prophylaktische Verhütung von Arteriosklerose untersucht haben.…”
Section: Kann Arterioskleroseimpfung Für Die Klinische Anwendung Entwunclassified